Manhaj as Epistemological Foundation: Rethinking Da'wah Messages in Salafi Communities, West Sumatra - Afandi, Yusuf; Bukhari; Andri Ashadi (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article aims to identify and conceptualize the “manhaj” message as an epistemological category within Salafi da’wah practices in West Sumatra. This study is an extension of existing theories of da’wah messages, which have so far been limited to the aspects of 'aqidah, sharia, and akhlak, while the aspects that shape religious practice and the formation of a framework of thought in understanding religious teachings have not yet received attention from experts and academics in the field of da’wah. Using a qualitative exploratory-conceptual approach, the author collected data from various studies on Salafi da'wah in West Sumatra through interviews, observations, and documentation of various online and offline studies conducted by the Salafi da'wah community. This study found that the